Nurses Knowledge and Practices Regarding Tracheostomy Care in ICU Patients - Samina Nazir, Saima Riaz, Zahida Abbas, Shamim Akhtar, Waqas Latif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Tracheostomy care in ICU patients is a basic nursing procedure. It can lead to many complications and is associated with a lot of distress among clients. Study design: Cross sectional descriptive study. Methodology: Total of 75 nurses were recruited in study that involved ICU of three tertiary care hospitals in Lahore. Convenient sampling technique was used. For data collection a self-structured questionnaire was used. The collected data was analyzed by using SPSS version 25. Chi Outcome was applied with p-value of less than 0.05 as significant. Results: There was significant association (p-value <0.05) between nurses knowledge and practice regarding tracheostomy care in ICU patients. The majority of the nurses > 65% had adequate knowledge. Conclusion: The findings of the current study revealed, that nurses are having adequate level of knowledge and practices regarding tracheostomy in managing tracheostomy in ICU patients. Hence, health care settings are required to provide organized clinical guidelines and protocols for patient’s safety.